2019
DOI: 10.1109/tii.2019.2902274
|View full text |Cite
|
Sign up to set email alerts
|

Fault Detection and Isolation in Industrial Processes Using Deep Learning Approaches

Abstract: Automated fault detection is an important part of a quality control system. It has the potential to increase the overall quality of monitored products and processes. The fault detection of automotive instrument cluster systems in computerbased manufacturing assembly lines is currently limited to simple boundary checking. The analysis of more complex nonlinear signals is performed manually by trained operators, whose knowledge is used to supervise quality checking and manual detection of faults. We present a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(50 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…In a different setting, fault detection for computer-based assembly lines of the automotive industry was studied in Reference [59]. This process is usually performed through boundary checking while the analysis of complex non-linear signals is manually performed by experienced personnel.…”
Section: Deep Learning-based Solutionsmentioning
confidence: 99%
“…In a different setting, fault detection for computer-based assembly lines of the automotive industry was studied in Reference [59]. This process is usually performed through boundary checking while the analysis of complex non-linear signals is manually performed by experienced personnel.…”
Section: Deep Learning-based Solutionsmentioning
confidence: 99%
“…However, Hadi et al [5] used an RNN model-based fault diagnosis technique with a time step of 1 to detect faults without such data. Rahat et al [7] used a deep autoencoder [15] and Artificial Neural Network (ANN) to provide various data for fault detection in the industry, and its performance was twice as high as the conventional rule-based method. Lee et al [16] detected more than 95% of the faults in an Air Handling Unit (AHU) using five hidden layers with 200 neurons.…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, studies have been actively attempting to integrate artificial intelligence technology with such systems to improve the intelligence and utilization of sensors. In particular, research is underway to reduce energy by forecasting the energy demand and supply [6], designing automatic fault detection technology using deep learning methods [5,7], and developing smart sensors with artificial intelligence (AI) [8]. Because the data used to train the AI come from the sensors, they are essential for enhancing the intelligence of buildings.…”
Section: Introductionmentioning
confidence: 99%
“…In the finance domain, machine learning is often applied in the credit risk prediction, 11 investment behavior estimation, 12 and financial products pricing 13 . In the assembly domain, machine learning is an emerging technology for the quality diagnosis, 14 fault detection, 15 and automated learning from demonstrations 16 . According to the above reviews, it can be concluded that machine learning is a hotspot to address short‐term prediction or classification tasks in engineering, but the real‐time and dynamic changing environment in engineering puts forward higher requirements for the decision‐making ability of the system or robot.…”
Section: Introductionmentioning
confidence: 99%